Corona fatality development and the environment: Empirical evidence for OECD countries - Lucas Bretschger; Elise Grieg; Paul J. J. Welfens; Tian Xiong (ETH Zurich, CER-ETH - Center of Economic Research, 2020)
This paper presents empirical results on coronavirus fatality rates from cross-country regressions for OECD countries. We include medical, environmental and policy variables in our analysis to explain the death rates when holding case rates constant. We find that the share of the aged population, obesity rates, and local air pollution levels have a positive effect on fatality rates across the different estimation equations. The strategy of aiming to achieve herd immunity has a significant positive effect on death rates. Other medical and policy variables discussed in the public sphere do not show a significant impact in our regressions. An evaluation of different health policy stringencies does not yield clear conclusions. Our results suggest that improving local air quality helps reduce the negative effects of a coronavirus pandemic significantly.
Keywords: I10; Q53; I18; H12; 330; Coronavirus Pandemic; Fatality Rates; Local Air Pollution; OECD Countries; Health Systems; Environmental Policy